Control of nitrogen doping in NaTaO3 synthesized by hydrothermal reaction and chemical state of nitrogen. (13th September 2018) - Ozawa, Akiyo; Kobayashi, Keita; Yoshida, Tomoko
Abstract : Nitrogen‐doped NaTaO3 was synthesized through 1‐pot reaction, hydrothermal process using Ta3 N5 as precursor. Changing concentration and amount of NaOH aqueous solution influenced nitrogen content in NaTaO3 . Absorption edge of nitrogen‐doped NaTaO3 was extended at 570 nm, and absorbance in visible light region depended on nitrogen content in NaTaO3 . Anodic photocurrent measured under visible light irradiation became larger with increasing nitrogen content in NaTaO3‐ x N y . Under ultraviolet light irradiation ( λ  ≤ 400 nm), the highest anodic photocurrent was observed when nitrogen concentration was y  = 0.024. It was possible to expand the wavelength range that can be effectively utilized for the photoelectrochemical reaction.